2017
DOI: 10.2174/1874070701711010054
|View full text |Cite
|
Sign up to set email alerts
|

Biomethanization of the Mixture of Cattle Manure, Pig Manure and Poultry Manure in Co-Digestion with Waste Peels of Pineapple Fruit and Content of Chicken-Gizzard - Part II: Optimization of Process Variables

Abstract: Background:The indiscriminate discharge of industrial waste, agricultural-biomass waste, waste of municipal, domestic and kitchen waste has negatively impacted on the environment and human health. It is very pertinent to reduce these impacts to the barest minimum through conversion of the waste to useful products. The conversion of these wastes to generate alternative energy to fossil fuel through the technology of anaerobic fermentation is one of the viable and more fascinating options for the management of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…There was no published research investigating the dependence of hydrogen production on hydrogen sulphide emission. Another relevant case showed that for efficient methane production, it was not necessary to supplement nutrients like in Aworanti et al’s work (Aworanti et al 2017 ). The high hydrogen production did not occur as in Elreedy et al ( 2017 ) because the research was only glycol ethylene without petrochemical wastes.…”
Section: Resultsmentioning
confidence: 99%
“…There was no published research investigating the dependence of hydrogen production on hydrogen sulphide emission. Another relevant case showed that for efficient methane production, it was not necessary to supplement nutrients like in Aworanti et al’s work (Aworanti et al 2017 ). The high hydrogen production did not occur as in Elreedy et al ( 2017 ) because the research was only glycol ethylene without petrochemical wastes.…”
Section: Resultsmentioning
confidence: 99%
“…Wichitsathian et al [182] also reported that pineapple waste's specific gas production rate increased from 132.05 L/kg of VS to 866.75 L/kg of VS after pretreatment was applied. For instance, the study by Aworanti et al [183] on the methane potential from the co-digestion of pineapple peels and manures and the optimisation of process parameters such as temperature, solid content and substrate to inoculum ratio discovered that by operating the co-digestion process at 55.2 • C, 6.25% solid content and 1:2 substrate to inoculum ratio could produce a high biogas yield with 71.10% methane content. In a different study, Aworanti et al [184] investigated the influence of substrate to inoculum ratio, temperature and agitation speed on anaerobic digestion of pineapple wastes and manure.…”
Section: Biogasmentioning
confidence: 99%
“…ACCESS Freely available online and fat), types of chemical (catalyst and methanol), operating condition, free fatty acid and alcohol to oil ratio [6,13]. Types of catalyst used for transesterification reaction in biodiesel production are homogeneous and heterogeneous catalysts, the homogeneous catalysts are classified into two such as acid and base catalysts while the heterogeneous are classified into three such as acid, base, and enzymatic catalysts, the rate of reaction for base-catalyzed transesterification is higher and produce high amount of biodiesel at reduced reaction time than that catalyzed with acidic catalyst, while enzyme catalyst is a good catalyst for transesterification due to it moderate temperature and high yield but it is expensive, therefore the preferred process for biodiesel production is homogeneous alkaline transesterification because the catalyst is faster and cheaper than other catalysts [2,14,15]. Sodium hydroxide and potassium hydroxide are the most used homogenous alkaline catalyst, these catalysts have high conversion at mild conditions and reduced reaction time and the advantages of homogeneous catalysts over heterogeneous catalysts are less corrosive, quantity of alcohol required is small, and not required sophisticated reactors [16].…”
Section: Openmentioning
confidence: 99%
“…The transesterification reaction for the production of biodiesel from treated waste frying oil (WFVO and WFPO) was carried out in accordance with the procedure of Aworanti et al [2]. Onefactor-at-a time (OFAT) approach was used to evaluate the possible optimum level of the operating parameters that can be used for the production of maximum biodiesel fuel yield.…”
Section: Experimental Design: Transesterification Of Treated Waste Frmentioning
confidence: 99%
See 1 more Smart Citation